Bacteriome-Associated Endosymbiotic Bacteria of Nosodendron Tree Sap Beetles (Coleoptera: Nosodendridae) - Hirota, Bin; Meng, Xian-Ying; Fukatsu, Takema (Frontiers in Microbiology, 2020)
The family Nosodendridae is a small group of tree sap beetles with only 91 described species representing 3 genera from the world. In 1930s, bacteria-harboring symbiotic organs, called bacteriomes, were briefly described in a European species Nosodendron fasciculare. Since then, however, no studies have been conducted on the nosodendrid endosymbiosis for decades. Here we investigated the bacteriomes and the endosymbiotic bacteria of Nosodendron coenosum and Nosodendron asiaticum using molecular phylogenetic and histological approaches. In adults and larvae, a pair of slender bacteriomes were found along both sides of the midgut. The bacteriomes consisted of large bacteriocytes at the center and flat sheath cells on the surface. Fluorescence in situ hybridization detected preferential localization of the endosymbiotic bacteria in the cytoplasm of the bacteriocytes. In reproductive adult females, the endosymbiotic bacteria were also detected at the infection zone in the ovarioles and on the surface of growing oocytes, indicating vertical symbiont transmission via ovarial passage. Transmission electron microscopy unveiled bizarre structural features of the bacteriocytes, whose cytoplasm exhibited degenerate cytology with deformed endosymbiont cells. Molecular phylogenetic analysis revealed that the nosodendrid endosymbionts formed a distinct clade in the Bacteroidetes. The nosodendrid endosymbionts were the most closely related to the bacteriome endosymbionts of bostrichid powderpost beetles and also allied to the bacteriome endosymbionts of silvanid grain beetles, uncovering an unexpected endosymbiont relationship across the unrelated beetle families Nosodendridae, Bostrichidae and Silvaniidae. Host-symbiont co-evolution and presumable biological roles of the endosymbiotic bacteria are discussed.